Catalyst recycling in monophasic Pt-catalyzed hydrosilylation reactions using ionic liquids - Taccardi, Nicola; Fekete, Melinda; Berger, Markus; Stanjek, Volker; Schulz, Peter; Wasserscheid, Peter (Applied Catalysis A-General, 2011)
The technical relevant Pt-catalyzed hydrosilylation of allyl chloride with trichlorosilane was investigated in a monophasic reaction system containing an ionic liquid (IL) additive. ILs screening allowed us to identify the liquid 1-decyl-3-methylimidazolium bis(trifloromethanesulfonyl)amide ([DMIM][NTf2]) as the best additive for such process. This IL combined complete miscibility with reactants as long as chemical and thermal robustness. After the reaction, the hydrosilylation product (3-chloropropyl)trichlorosilane was distilled off and the residual IL/catalyst solution could be reused. In such a way, a final TON of 14,200 was achieved over 10 reaction/distillation cycles without any loss of catalytic activity. The ability of [DMIM][NTf2] to prevent catalyst decomposition was deeper investigated and it was found that even with a Pt loading as high as 9500 ppm, the IL acted as protective/stabilizing agent for the catalyst during the thermally stressing product distillation.

Catalytic production of hydrogen from glucose and other carbohydrates under exceptionally mild reaction conditions - Taccardi, Nicola; Assenbaum, Daniel; Berger, Markus; Bösmann, Andreas; Enzenberger, Florian; Woelfel, Rene; Neuendorf, Stephanie; Göke, Volker; Schödel, Nicole; Maaß, Hans-Jürgen; Kistenmacher, Hans; Wasserscheid, Peter (Green Chemistry, 2010)
A catalytic reaction system for the production of hydrogen from sugars and even water-insoluble biomass like cellulose is presented. The reaction system is based on an ionic liquid that has the role to dissolve the carbohydrate feedstock and a ruthenium catalyst. As hydrogen dissolves in this media at very low level, hydrogen consuming side reactions have been hindered, leading to a gaseous product mixture consisting mainly of hydrogen and carbon dioxide. Investigations with isotopic labelling suggest a reaction sequence in which glucose first thermally decomposes to formic acid followed by Ru-catalyzed decomposition of the latter to hydrogen and CO_2.

Simple and recyclable ionic liquid based system for the selective decomposition of formic acid to hydrogen and carbon dioxide - Berger, Markus; Assenbaum, Daniel; Taccardi, Nicola; Spiecker, Erdmann; Wasserscheid, Peter (Green Chemistry, 2011)
Exploitation of hydrogen as an energy carrier requires the development of systems for its storage and delivery. Formic acid has been proposed as valuable hydrogen carrier compound, due to its relatively high hydrogen content (53 g L-1), the latter being easily and cleanly released in catalytic reactions under mild conditions (HCOOH → H_2 + CO_2). Ionic liquids are interesting solvents for homogeneous catalyzed formic acid decomposition systems as their extremely low volatility avoids solvent contamination of the produced hydrogen stream. In this paper an outstandingly simple, robust and active catalyst system is presented, namely RuCl_3 dissolved in 1-ethyl-2,3-dimethylimidazolium acetate (RuCl_3/[EMMIM][OAc]). This system proved to be fully recyclable over 10 times. Turnover frequencies (TOF) of 150 h-1 and 850 h-1 were obtained at 80 °C and 120 °C, respectively.

Viscosity, Interfacial Tension, Self-Diffusion Coefficient, Density, and Refractive Index of the Ionic Liquid 1-Ethyl-3-methylimidazolium Tetracyanoborate as a Function of Temperature at Atmospheric Pressure. - Koller, Thomas Manfred; Rausch, Michael Heinrich; Schulz, Peter; Berger, Markus; Wasserscheid, Peter; Economou, Ioannis G.; Leipertz, Alfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2012)
Thermophys. properties of the ionic liq. (IL) [EMIM][B(CN)4] (1-ethyl-3-methylimidazolium tetracyanoborate) were investigated both by conventional techniques and by surface light scattering (SLS) at atm. pressure. The d. was measured between (283.15 and 363.15) K with a vibrating U-tube densimeter. An Abbe refractometer was used for the measurement of the refractive index in the range from (283.15 to 313.15) K. Self-diffusion coeffs. for the cation and anion were measured by NMR spectroscopy from (273.15 to 318.15) K. The interfacial tension was obtained from the pendant drop technique at 297.04 K. Based on this datum and the temp. dependence of d., the interfacial tension for all relevant temps. was estd. via an appropriate prediction model. For the IL studied within the present work, the quantity directly accessible by SLS at low temps. was the ratio of dynamic viscosity to interfacial tension. Combining the results from SLS with the d. and interfacial tension data obtained from conventional methods, the dynamic viscosity could be detd. from (283.15 to 303.15) K. For higher temps., SLS measurements combined with the results for d. allowed the simultaneous detn. of dynamic viscosity and interfacial tension from (313.15 to 363.15) K. Besides a comparison with literature data for [EMIM][B(CN)4], the influence of variation of the anion in [EMIM]-based ILs on thermophys. properties is discussed. It could be shown that the thermophys. properties of [EMIM][B(CN)4] are mainly affected by the distinct charge delocalization in the anion. [on SciFinder(R)]
Keywords: viscosity interfacial tension diffusion density refractive index ethylmethylimidazolium tetracyanoborate